2013
DOI: 10.1002/oby.20128
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum leptin during pregnancy and infant birth weight: The influence of maternal overweight and obesity

Abstract: Few studies have examined whether the distinct metabolic patterns found in obese and non-obese pregnant women may have different effects on the growing fetus. Our objective was to estimate the influence of longitudinal variation in maternal serum leptin levels on variation in infant birth weight in overweight/obese versus normal weight women. In a prospective cohort of 286 gravidas, we measured maternal weight and serum leptin levels at 6–10,10–14,16–20, 22–26, and 32–36 weeks gestation. Effects of leptin leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 42 publications
6
38
5
Order By: Relevance
“…As less invasive measures are developed, such as maternal serum leptin, the use of amniocentesis may continue to decrease, identifying a need for correlation between measures. 33 Efforts to combine genetic information with clinical biomarkers, including potentially nutritional assessments, promises to improve the prediction and treatment of fetal growth abnormalities. [34][35][36] Leptin has the potential of being a biomarker that can predict abnormal patterns of fetal growth, the potential to refine prognosis and better predict neonatal outcomes, potentially impacting morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…As less invasive measures are developed, such as maternal serum leptin, the use of amniocentesis may continue to decrease, identifying a need for correlation between measures. 33 Efforts to combine genetic information with clinical biomarkers, including potentially nutritional assessments, promises to improve the prediction and treatment of fetal growth abnormalities. [34][35][36] Leptin has the potential of being a biomarker that can predict abnormal patterns of fetal growth, the potential to refine prognosis and better predict neonatal outcomes, potentially impacting morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort study, Misra et al [15] found no association between the magnitude of variation in maternal leptin concentration and variation in infant birth weight, a surrogate measure of FM%. However, an increase in the rate of change in maternal serum leptin in the second half of pregnancy was associated with a reduction in birth weight in overweight/obese pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Weight gain, hyperglycemia, insulin resistance, and altered leptin and adiponectin concentrations are common effects observed in both pregnancy and obesity. Maternal leptin levels increase during pregnancy [15,16], possibly as a consequence of placental production and fat mass gain. Adiponectin levels decrease throughout pregnancy [17,18] and are inversely related to adiposity gain.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that increased levels of these inflammatory markers in the neonatal systemic circulation as well as their direct transmission through the placental barrier may affect the neonate [30]. Since incremental weight gain has been associated with higher leptin levels [31] and systemic inflammation, and we observed a linear trend between maternal BMI and neonatal outcomes observed in our study, we speculate that increasing systemic inflammation with increasing maternal BMI may play a role in the higher incidence and trends of neonatal morbidities observed in our study. Further studies are needed to investigate this potential mechanism.…”
Section: Discussionmentioning
confidence: 99%